Incentive Effects of Subjective Allocations of Rewards and Penalties - Cai, Wei; Gallani, Susanna; Shin, Jee-Eun (Management Science, 2023)
We examine the incentive effects of subjectivity in allocating tournament-based rewards and punishments. We use data from a company where reward and punishment decisions are based on a combination of objective metrics and subjective performance assessments. Rankings based on the objective metrics and the ultimate payoff allocations are disclosed to all members of the organization. This information allows employees to observe whether and how managers subjectively override the objective rankings. Consistent with expectancy theory, we predict and find that subjective rewards and punishments manifesting as favorable (unfavorable) deviations from formula-based payoff expectations are associated with subsequent performance improvements (declines). These performance responses are incremental to the effects of receiving a reward or punishment per se. Our results suggest that managers can benefit from using subjective rewards, but using subjective punishments can be very costly in the absence of sufficiently strong ex ante incentive effects associated with the prospect of subjective penalties. Our findings contribute to the literature on subjectivity in performance evaluations and have important practical implications for designing incentive systems. This paper was accepted by Brian Bushee, accounting. Funding: The authors appreciate the Harvard Business School for financial support during the development of this study. Supplemental Material: Data are available at https://doi.org/10.1287/mnsc.2022.4501 .